Multi-omics analysis of the rhizosphere effects and molecular mechanisms of Ageratum conyzoides linn. at different stages of Cd, Pb, and Zn co-stress - Yuexin Fu; Mouyixing Chen; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu; Shaohong You (Journal of Environmental Management, 2026)

Dual-mode colorimetric and fluorescent pH sensor based on carbon dots for real-time monitoring of shrimp freshness - Ke Zhang; Pingping Wang; Haiming Chen; Chun Chen; Xiong Fu (Food Packaging and Shelf Life, 2026)

Species-specific environmental niches govern biogeographic patterns and seasonal dynamics of the harmful algal genus Phaeocystis in Chinese seas - Pingping Shen; Jiayi Shi; Xuejun Fu; Qingshang Song; Yue Xue; Xiyan Wang; Mengqi Dong; Haiping Li (Environmental Pollution, 2026)

Ultrasonic degradation of Dendrobium officinale polysaccharide: Kinetics, structural modification, and its impact on wheat starch digestibility - Jinfeng Fu; Xiong Fu; Pingping Wang; Yuxuan Fu; Chun Chen (Food Research International, 2026)

Multi-component catalysts with three-dimensional porous structures for exhaust gas purification: Activity for soot and CO - Xiaolong Sheng; Li Li; Changcheng Fu; Peng Zhang; Lefu Yang; Mingzhang Pan; Jinkai Gu; Pingping Huang; Yupei Yang; Tian Zhang; Wei Guan (Journal of Environmental Chemical Engineering, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

The coordination level of multi-actor environmental governance: marketization, technological innovation, and corruption - Yanhong Tang; Muzi Chi; Ruixue Yan; Weina Zhang; Yujing Zhao; Pingping Fu (Clean Technologies and Environmental Policy, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Preparation of pitch-based carbon fiber from medium coal tar pitch refined by wash oil - Pingping Zuo; Shaobo Fu; Xiaoqiang He; Hongxian Niu; Shijie Qu; Wenzhong Shen (Fuel, 2025)

Extracellular vesicles derived from “serum and glucose” deprived HUCMSCs promoted skin wound healing through enhanced angiogenesis - Xiaopeng Wu; Pingping Yuan; Na Wei; Chaoqun Ma; Mingdi Fu; Wei Wu (Molecular and Cellular Biochemistry, 2025)

Study on Elastoplastic Damage Constitutive Model and Permeability Evolution Law of Gas-Bearing Coal - Jiale Fu; Bobo Li; Chonghong Ren; Qiaoyun Cheng; Pingping Ye; Sandong Zhou (Rock Mechanics and Rock Engineering, 2024)

Performance of loach to reduce clogging matter in vertical-flow constructed wetlands: Hydraulic evaluation and metabolic processes - Xiuzheng Fu; Fanlong Kong; Pingping Duan; Fanyi Li; Wenxuan Hu; Xiaomin Liu; Zhengda Yu; Yuqian Cui (Chemical Engineering Journal, 2024)

Atmospheric water demand dominates terrestrial ecosystem productivity in China - You Tu; Xiaofeng Wang; Jitao Zhou; Xiaoxue Wang; Zixu Jia; Jiahao Ma; Wenjie Yao; Xinrong Zhang; Zechong Sun; Pingping Luo; Xiaoming Feng; Bojie Fu (Agricultural and Forest Meteorology, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

Investigation on damage-permeability model of dual-porosity coal under thermal-mechanical coupling effect - Pingping Ye; Bobo Li; Chonghong Ren; Haosheng Song; Jiale Fu; Xuehai Wu (Gas Science and Engineering, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Quantitative assessment of spatiotemporal dynamics in vegetation NPP, NEP and carbon sink capacity in the Weihe River Basin from 2001 to 2020 - Jiqiang Lyu; Xianghang Fu; Chen Lu; Yueyan Zhang; Pingping Luo; Peng Guo; Aidi Huo; Meimei Zhou (Journal of Cleaner Production, 2023)

Application of an integrated loach-plant-substrate-microbes non-aerated saturated vertical flow constructed wetlands: Mechanisms of pollutants removal and greenhouse gases reduction - Xiuzheng Fu; Zhengda Yu; Fanlong Kong; Pingping Duan; Fanyi Li; Lingzhu Zhang; Zhongying Liu; Yuqian Cui (Bioresource Technology, 2023)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Assessing the environmental impact of China’s tourism activities: a tourism heat footprint method - Shuxin Wang; Weihong Cao; Jiankuo Du; Pingping Tang; Hengyang Fu; Zi Tang; Jiamei Li (Environmental Science and Pollution Research, 2021)

Local environmental selection and lineage admixture act as significant mechanisms in the adaptation of the widespread East Asian pond skater Gerris latiabdominis to heterogeneous landscapes - Zhen Ye; Juanjuan Yuan; Yahui Zhen; Jakob Damgaard; Kazutaka Yamada; Xiuxiu Zhu; Kun Jiang; Xin Yang; Wenwu Wang; Shujing Wang; Jingyu Liang; Siying Fu; et al. (Journal of Biogeography, 2020)
Aim Local environmental selection and lineage admixture have long been accepted as important adaptive mechanisms in adjusting widespread taxa to new environments. We studied a pond skater, Gerris latiabdominis , to explore the relative roles played by these two mechanisms in its process of adaptation to heterogeneous landscapes. Location East Asia. Taxon Gerris latiabdominis Miyamoto, 1958. Methods Mitochondrial (COI, COII) and nuclear (ddRAD‐seq) markers were sequenced from 202 individuals. Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. The demographical history was simulated by approximate Bayesian computation (ABC). The single‐nucleotide polymorphisms (SNPs) that may have been subjected to natural divergent selection among the populations were assessed, and the recent migration rates were estimated. Finally, shifts in suitable habitat from the last interglacial (LIG) to the present were predicted through ecological niche modelling (ENM). Results We found population structures inferred from both mitochondrial and nuclear genomes to be almost coincident and to correspond to temporal or spatial heterogeneity. The early Pliocene splitting event between the northern (NO) and southeastern (SE) groups is consistent with the ‘arid belt hypothesis’, followed by local environmental selection. Approximate Bayesian computation and gene flow estimation strongly suggested that the southwestern (SW) groups originated from a lineage admixture event between the SE and western (WE) groups and subsequently underwent ongoing gene flow from the SE group during the Pleistocene. The mito‐nuclear discordance pattern in the SW group was probably due to the ancient mitochondrial differentiation. Main conclusion Our results suggest that both local environmental selection and lineage admixture acted as significant mechanisms of G. latiabdominis adaptation to heterogeneous landscapes in East Asia. Furthermore, this study showed that conclusions based exclusively on mitochondrial data might mislead taxonomic, phylogenetic and phylogeographical studies.

Interactions between ultraviolet radiation exposure and phosphorus limitation in the marine nitrogen‐fixing cyanobacteria Trichodesmium and Crocosphaera - Zhu Zhu; Feixue Fu; Pingping Qu; Esther Wing Kwan Mak; Haibo Jiang; Ruifeng Zhang; Zhuoyi Zhu; Kunshan Gao; David A. Hutchins (Limnology and Oceanography, 2020)
Increased stratification and mixed layer shoaling of the surface ocean resulting from warming can lead to exposure of marine dinitrogen (N 2 )‐fixing cyanobacteria to higher levels of inhibitory ultraviolet (UV) radiation. These same processes also reduce vertically advected supplies of the potentially limiting nutrient phosphorus (P) to N 2 fixers. It is currently unknown how UV inhibition and P limitation interact to affect the biogeochemical cycles of nitrogen and carbon in these biogeochemically critical microbes. We investigated the responses of the important and widespread marine N 2 ‐fixing cyanobacteria Crocosphaera (strain WH0005) and Trichodesmium (strains IMS 101 and GBR) to UV‐A and UV‐B under P‐replete and P‐limited conditions. Growth, N 2 fixation, and carbon dioxide (CO 2 ) fixation rates of Trichodesmium IMS 101 and Crocosphaera were negatively affected by UV exposure. This inhibition was greater for Trichodesmium IMS 101 than for Crocosphaera , which fixes N 2 only during the night and so avoids direct UV damage. Negative effects of UV on both IMS 101 and Crocosphaera were less in P‐limited cultures than in P‐replete cultures. In contrast, no UV inhibition was observed in GBR, regardless of P availability. UV inhibition was related to different amounts of UV‐absorbing compounds produced by these isolates. Responses to UV radiation and P availability interactions were taxon‐specific, but our results indicated that in general, UV radiation effects on Trichodesmium and Crocosphaera range from negative to neutral. UV inhibition and its interactions with P limitation may thus have a substantial influence on the present day and future nitrogen and carbon cycles of the ocean.

Extracellular production of recombinant N-glycosylated anti-VEGFR2 monobody in leaky Escherichia coli strain - Ning Ding; Xin Fu; Yao Ruan; Jing Zhu; Pingping Guo; Lichi Han; Jianing Zhang; Xuejun Hu (Biotechnology Letters, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Species Diversity and Functional Prediction of Soil Bacterial Communities in Constructed Wetlands with Different Plant Conditions - Weiguo Fu; Yuxuan Wang; Wei Wei; Pingping Li (Current Microbiology, 2019)

Responses of the large centric diatom Coscinodiscus sp. to interactions between warming, elevated CO 2 , and nitrate availability - Pingping Qu; Feixue Fu; David A. Hutchins (Limnology and Oceanography, 2018)
Marine ecosystems are facing multiple anthropogenic global changes, including ocean acidification, warming, and reduced nutrient supplies. Together, these will challenge phytoplankton including large centric diatoms such as Coscinodiscus sp., a group that is important to ocean food webs and carbon export. We investigated the interactive effects of warming, elevated CO 2 , and nitrate availability on Coscinodiscus growth, elemental stoichiometry, and Fe and C uptake rates in a four‐treatment factorial experiment combining two CO 2 levels (∼400 ppm and 800 ppm) and two temperatures (16°C and 20°C) across seven nitrate concentrations (1–100 μ mol L −1 ). Higher temperatures led to higher maximum growth rates ( μ max ), but also higher half‐saturation constants for nitrate ( K 1/2 ), while elevated CO 2 increased K 1/2 only at the warmer temperature. Lower μ max / K 1/2 ratios under warming and rising CO 2 indicated a higher nitrate requirement at these conditions. High temperature decreased cellular P and Si contents and consequently increased N : P and C : Si ratios, especially at ambient CO 2 . Fe : C uptake ratios responded positively to lower nitrate levels, lower CO 2 , and warming. Significant interactions between nitrate availability and temperature or CO 2 were observed for specific growth rates, chlorophyll a and Si contents, Fe : C, N : P, and Si : C, while temperature and CO 2 interactions were only significant for μ max / K 1/2 and cellular P content. The mutual interactions among CO 2 concentrations, temperature, and nitrate supply may all affect future growth, physiology, and carbon export by Coscinodiscus sp., however, in general warming and nitrate availability appear to be more influential than CO 2 .

Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae) - Zhen Ye; Juanjuan Yuan; Min Li; Jakob Damgaard; Pingping Chen; Chenguang Zheng; Haibin Yu; Siying Fu; Wenjun Bu (Journal of Biogeography, 2018)
Aim Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis , to explore the relative roles played by these two factors in population genetic connectivity. Location Sichuan Basin, China. Methods Mitochondrial ( COI , COII , Cytb, 16S) and nuclear ( EF ‐1α, ITS 1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum ( LGM ) to the present were predicted through fine‐tuned ecological niche modelling ( ENM ). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated using beast . Finally, the least cost path ( LCP ) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot ( BSP ) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis , in global biodiversity hotspots is proposed and discussed in this paper.

Persistence Parameter: a Reliable Measurement for Behavioral Responses of Medaka (Oryzias latipes) to Environmental Stress - Li Yin; Haitang Yang; Guiyun Si; Qing Ren; Rongshu Fu; Biao Zhang; Xu Zhang; Xiaoguang Wang; Pingping Qi; Chunlei Xia; Zongming Ren; Tae-Soo Chon; et al. (Environmental Modeling & Assessment, 2016)

Metabolomic Analysis Revealed Differential Adaptation to Salinity and Alkalinity Stress in Kentucky Bluegrass (Poa pratensis) - Longxing Hu; Pingping Zhang; Ying Jiang; Jinmin Fu (Plant Molecular Biology Reporter, 2015)

Slow decomposition and limited nitrogen release by lower order roots in eight Chinese temperate and subtropical trees - Yanmei Xiong; Pingping Fan; Shenglei Fu; Hui Zeng; Dali Guo (Plant and Soil, 2013)

Effects of alkali stress on growth, free amino acids and carbohydrates metabolism in Kentucky bluegrass (Poa pratensis) - Pingping Zhang; Jinmin Fu; Longxing Hu (Ecotoxicology, 2012)

Mechanism of the plant community succession process in the Zhenjiang Waterfront Wetland - Weiguo Fu; Pingping Li; Yanyou Wu (Plant Ecology, 2011)